High virologic response rate after second-line boosted protease inhibitor-based antiretroviral therapy regimens in children from a resource limited setting - Thanyawee Puthanakit (2018)
Background: Limited data exist for the efficacy of second-line antiretroviral therapy among children in resource limited settings. We assessed the virologic response to protease inhibitor-based ART after failing first-line non-nucleoside reverse transcriptase inhibitor (NNRTI)-based regimens.Methods: A retrospective chart review was conducted at 8 Thai sites of children who switched to PI -based regimens due to failure of NNRTI -based regimens. Primary endpoints were HIV RNA < 400 copies/ml and CD4 change over 48 weeks.Results: Data from 241 children with median baseline values before starting PI-based regimens of 9.1 years for age, 10% for CD4%, and 4.8 log 10 copies/ml for HIV RNA were included; 104 (41%) received a single ritonavir-boosted PI (sbPI) with 2 NRTIs and 137 (59%) received double-boosted PI (dbPI) with/without NRTIs based on physician discretion. SbPI children had higher baseline CD4 (17% vs. 6%, p < 0.001), lower HIV RNA (4.5 vs. 4.9 log 10 copies/ml, p < 0.001), and less frequent high grade multi-NRTI resistance (12.4% vs 60.5%, p < 0.001) than the dbPI children. At week 48, 81% had HIV RNA < 400 copies/ml (sbPI 83.1% vs. dbPI 79.8%, p = 0.61) with a median CD4 rise of 9% (+7%vs. + 10%, p < 0.005). However, only 63% had HIV RNA < 50 copies/ml, with better viral suppression seen in sbPI (76.6% vs. 51.4%, p 0.002).Conclusion: Second-line PI therapy was effective for children failing first line NNRTI in a resource-limited setting. DbPI were used in patients with extensive drug resistance due to limited treatment options. Better access to antiretroviral drugs is needed. © 2012 Puthanakit et al.; licensee BioMed Central Ltd.